2006
DOI: 10.1007/s00125-005-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sodium increase and susceptibility to ischaemia in hearts from type 2 diabetic db/db mice

Abstract: Aims/hypothesis: An important determinant of sensitivity to ischaemia is altered ion homeostasis, especially disturbances in intracellular Na + Na þ i À Á handling. As no study has so far investigated this in type 2 diabetes, we examined susceptibility to ischaemia-reperfusion in isolated hearts from diabetic db/db and control db/+ mice and determined whether and to what extent the amount of Naincrease during a transient period of ischaemia could contribute to functional alterations upon reperfusion. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 42 publications
(53 reference statements)
4
39
0
Order By: Relevance
“…This is consistent with the data from comparable heart failure models that link increased CaMKII␦ with higher SR Ca 2ϩ leak, and that show inhibition of CaMKII␦, but not PKA, abolishes the leak. 11,26 db/db mice are more prone to arrhythmias, 27 but the underlying mechanisms are unknown. Increased SR Ca 2ϩ leak and increased NCX activity have been suggested as changes that would promote arrhythmias in whole hearts 10 ; exercise training could therefore be an effective treatment for arrhythmias in diabetes.…”
Section: The Potential Of Exercise Training To Reverse Mechanical Celmentioning
confidence: 99%
“…This is consistent with the data from comparable heart failure models that link increased CaMKII␦ with higher SR Ca 2ϩ leak, and that show inhibition of CaMKII␦, but not PKA, abolishes the leak. 11,26 db/db mice are more prone to arrhythmias, 27 but the underlying mechanisms are unknown. Increased SR Ca 2ϩ leak and increased NCX activity have been suggested as changes that would promote arrhythmias in whole hearts 10 ; exercise training could therefore be an effective treatment for arrhythmias in diabetes.…”
Section: The Potential Of Exercise Training To Reverse Mechanical Celmentioning
confidence: 99%
“…(Baetz et al, 2003). Accordingly, the effects of F 15845 on [Na ϩ ] i were investigated during global no-flow ischemia in normal and diabetic db/db mouse hearts (Anzawa et al, 2006). Isolated mouse hearts were subjected to 16 min of no-flow ischemia, and [Na ϩ ] i was monitored using 23 Na nuclear magnetic resonance spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The 23 Na spectra were recorded on an AM 400WB spectrometer (Bruker, Newark, DE) at 105.84 MHz, using a multinuclear NMR probe (Anzawa et al, 2006). Each 23 Na NMR spectrum was obtained by accumulation of 280 consecutive free induction decays using 90°p ulses and a 205-ms interpulse delay with a 2500-Hz spectral width and a 1-K data point time domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that development of diabetes leads to oxidative stress (Singal et al 2001;Maritim et al 2003) and defects in the cell sarcolemmal and sarcoplasmic reticular membranes, as well as to alterations in the function of ion transport systems (Na + /K + -and Ca 2+ -ATPase, Na + /H + and Na + /Ca 2+ exchangers and Ca 2+ channels). The latter leads to abnormal Na + and Ca 2+ handling in the diabetic myocardium that might compromise its tolerance to ischemia (Pierce et al 1990;Lee et al 1992;Dhalla et al 1998;Anzawa et al 2006).…”
Section: Ppar and Inflammationmentioning
confidence: 99%